Pre and postnatal characteristics of children and adolescents with intellectual disability - Antônio Augusto Schäfer; Lisiane Tuon Generoso Bitencourt; Bettina Stopazzolli Cassetari; Emily dos Santos Uggioni; Fernanda Oliveira Meller (Revista CEFAC, 2019)
ABSTRACT Purpose: to describe pre and postnatal characteristics of children and adolescents with intellectual disability. Methods: study performed with all individuals who received healthcare between August 2016 and February 2018 at a reference Rehabilitation Center which serves 27 towns and cities in the South of Santa Catarina State, Brazil. A questionnaire focusing on demographic, socioeconomic, pre and postnatal variables was administered to parents or guardians of children and adolescents by trained interviewers. Descriptive analyses were performed using absolute and relative frequencies of categorical variables and central tendency and dispersion measures of numerical variables. Results: 42 individuals in the mean age of 11 years (± 3.0) were studied. Most mothers reported having unintended pregnancy and more than a half reported having had a cesarean section. In addition, about one-fifth of the subjects had low birth weight and most of them received exclusive breastfeeding up to six months of age. Conclusion: these findings are crucial for the organization and improvement of health care services, since they provide evidence for health professionals to improve and/or focus their health care initiatives on these individuals.